Compact Circularly Polarized Monopole Antenna Using Characteristic Mode Analysis - Samineni Peddakrishna; Lulu Wang; Vamshi Kollipara; Jayendra Kumar (Proceedings of Engineering and Technology Innovation, 2023)
This study aims to design a circularly polarized compact antenna using characteristic mode analysis (CMA). The proposed antenna consists of a substrate with a slotted annular ring-shaped patch and partial ground. The excitation position of the antenna and its optimal dimensions are determined through the analysis of different operation modes with CMA. After that, an optimized antenna is designed, and an antenna prototype is fabricated for validation. The experimental results show that the reflection coefficient achieves a -10dB impedance bandwidth of 6.85 GHz, a 3dB-axial ratio bandwidth of 0.7 GHz, and a peak gain of 3.2 dBi. These characteristics agree with simulations and make the circularly polarized compact antenna suit for C-band and sub-6 GHz 5G wireless applications.